EEG-Microstates Reflect Auditory Distraction After Attentive Audiovisual Perception Recruitment of Cognitive Control Networks - Korn, Ute; Krylova, Marina; Heck, Kilian L.; Häußinger, Florian B.; Stark, Robert S.; Alizadeh, Sarah; Jamalabadi, Hamidreza; Walter, Martin; Galuske, Ralf A. W.; Munk, Matthias H. J. (Frontiers in Systems Neuroscience, 2021)
Processing of sensory information is embedded in ongoing neural processes which constitute brain states. Electroencephalographic (EEG) microstates (MS) are considered building blocks of consciousness and represent short segments of topographically stable electric brain activity patterns. MS are associated with resting state networks such as auditory, visual and attention networks. Some studies have shown that MSs can be influenced by vigilance level or neurological disorders like Schizophrenia or Alzheimer's disease. In order to get deeper insights, we investigated the effect of auditory distraction on memorization of visual and auditory information on EEG microstates - their duration, occurrence, contribution and transition rates during resting state recordings. As not much is known about cross modal effects on these MS parameters after challenging one sensory modality, we did not expect such systematic changes: brain microstates reflected a weakening of activity in the auditory system and strengthening of the salience network, supporting the idea that saliency networks are active after audio-visual encoding and during memorization to protect memories and concentrate on upcoming questions.